The effect of profitability and capital intensity on tax avoidance - Sitanggang, Tikkos; Leusiana, Silvi (Eximia, 2023)
This study aims to determine the effect of profitability and capital intensity on tax avoidance in coal mining sub-sector companies listed on the Indonesia Stock Exchange for the period 2019 to 2021. The population of this study totaled 24 companies and the sample used totaled 11 companies. The method used in this study is a quantitative research method with a descriptive research approach and panel data. Based on the test results show that profitability has a negative effect on tax avoidance. Meanwhile, capital intensity has no effect on tax avoidance. Simultaneously, profitability and capital intensity affect tax avoidance with a contribution of 63%, while the remaining 37% is influenced by other variables outside the study.